THE SIGNIFICANCE OF MUSIC IN THE DEVELOPMENT OF CHILDREN’S MEMORY (International Conference on Economics, Finance, Banking and Management, 2025)
This study investigates the cognitive significance of music in the development of children’s memory capacities. Drawing on contemporary neuroscientific and pedagogical research, it analyzes how musical engagement—particularly rhythmic patterns, melodic structures, and active participation—stimulates neural synchronization and enhances both short-term and long-term memory processes. The findings indicate that music not only improves auditory and verbal memory, but also strengthens attention, emotional regulation, and information-processing efficiency. The paper argues that integrating systematically designed musical activities into early childhood education can serve as an effective pedagogical strategy for supporting holistic cognitive development and improving memory performance in young learners.